PENGEMBANGAN BAHAN AJAR MATEMATIKA DISKRIT BERBASIS DIGITAL QR-CODE UNTUK MENINGKATKAN EFEKTIVITAS BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA INSTITUT PENDIDIKAN TAPANULI SELATAN - Harahap, Muhammad Syahril; Harahap, Sinar Depi; Nasution, Sari Wahyuni Rozi; Siregar, Dedes Asriani; Karolina, Elisa (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2023)
Abstract This study aims to determine the validity, practicality, and effectiveness of QR-Code-based digital teaching materials at the South Tapanuli Education Institute. The type of research used is development research using a 4-D development model. the stages of this research are (1) define or define; (2) design or design; (3) develop or development; (4) dissiminate or spread. The trial was conducted on fourth semester students of IPTS mathematics education. The results of this study indicate: 1) the validity of the QR-Code digital-based teaching materials at the South Tapanuli Education Institute is valid. 2) the practicality of QR-Code-based digital teaching materials at the South Tapanuli Education Institute is practical to use. 3) the effectiveness of QR-Code-based digital teaching materials at the South Tapanuli Education Institute is effectively used. This can be seen from the student response questionnaire. Keywords: development, QR-Code-based digital teaching materials